Difficulties in Pronouncing the English Consonant Sounds Among Grade 7 Students at KM/ST/Al-Marjan Muslim Ladies College (N/S), Sammanthurai, Ampara - M.S Najeema; M.J Fathima Sujani; MB Nowzath; M.R Rishad Muhammed (COMPETITIVE: Journal of Education, 2024)
This study was carried out with the aim of overcoming the difficulties confronted by grade 7 students of KM/ST/Al-Marjan Muslim Ladies college (N.S )Sammanthurai, Ampara in using pronunciation in appropriate place in communication. Because use correct pronunciation in communication has been a huge challenge for most of the grade 7 students at KM/ST/Al-Marjan Muslim Ladies college (N.S )Sammanthurai, Ampara. Therefore, 20 grade 7 students were randomly selected for data collection from the total population (60 students). This study was a qualitative research  and data collection method were qualitative. The research instruments of this study were observation and a test. According to the analysis of the observation, the findings show that most of the participants do not have the previous knowledge about consonants pronounce. They are majority aware of only ‘ /ch/ ’ ,/d/ ’, ‘ /g/’, ‘ /th/ ’ words. Most of them do not have ideas about ‘ /v/ ’, ‘ /w/ ’, ‘ /sh/ ’ , ‘ /s/ ’ , ‘ /l/ ’ , ‘ /r/ ’,‘ /x/ ’ and more. Further, according to the analysis of the test, a large amount of  the participants (13 participants) failed to ‘ /d/ ’, ‘ /g/ pronounce the sounds in the given words. Likewise, with regard to use of  ‘ /l/ ’ , ‘ /r/ ’ in words, the finding show that 8 participants correctly pronounce ‘ /l/ ’ , ‘ /r/ ’in only one word out of 5 places to pronounce ‘ /l/ ’ , ‘ /r/’ words. Moreover, no participants correctly pronounce ‘ /l/ ’ , ‘ /r/ ’ in all  five words. The reason is, students do not have the knowledge of pronunciations accurately in communication. This problem can be overcome when the followings are implemented such as teaching consonants pronunciation rules using deductive method, applying interesting pronouncing activities and games in the classroom, correcting students’ pronounce, strictly focusing on pronunciation error, giving reading practice and explaining the way the pronunciation have been used in communication.